1819-21 R.I. Pub. Laws 289, An Act To Prevent Certain Disorders In The Town Of Bristol, § 3 - (:unkn) unknown (General Publisher, 1819)
And be it further enacted, That if any person or persons shall, at any time hereafter, fire any gun or pistol in any of the streets, roads, lanes, buildings, or from any of the walls or fences thereto contiguous, and within the compact part of said town, without justifiable cause, such person or persons shall upon complaint and conviction thereof as aforesaid, pay a fine not less than two dollars nor more than four dollars for the first offense, and the sum of four dollars for each and every subsequent offence, to be paid and appropriated as aforesaid.
--
Keywords: DISCHARGE